1983
DOI: 10.1128/jcm.18.5.1040-1046.1983
|View full text |Cite
|
Sign up to set email alerts
|

Serogrouping and subtyping of Legionella pneumophila with monoclonal antibodies

Abstract: Monoclonal antibodies directed against Legionella pneumophila serogroups 1 to 6 were produced by fusing splenocytes of BALB/c mice with the Sp 2/0-Ag14 or the NSO mouse myeloma cell lines. Specificity of these antibodies was determined by indirect fluorescent-antibody staining: 8 reacted with L. pneumophila serogroup 1 and, respectively, 13, 6, 6, 5, and 10 reacted with serogroups 2, 3, 4, 5, and 6; all except 5 were serogroup specific, and none presented cross-reactions with six other species of Legionellacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…However, some of the anti-legionellae antibodies, even monoclonal ones, have the cross-reactivity to nonlegionellae such as Pseudomonas fluorescens, Bacteroides fragilis , or Xanthomonas sp. (2,6,11). Polyclonal antibodies-mixture for L. pneumophila serogroup 1 to 6 used in this survey reacted with several non-legionellae, but majority of their fluorescence were visibly distinguishable from the image of L. pneumophila under fluorescence microscopy, except E. coli GIFU 3160.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, some of the anti-legionellae antibodies, even monoclonal ones, have the cross-reactivity to nonlegionellae such as Pseudomonas fluorescens, Bacteroides fragilis , or Xanthomonas sp. (2,6,11). Polyclonal antibodies-mixture for L. pneumophila serogroup 1 to 6 used in this survey reacted with several non-legionellae, but majority of their fluorescence were visibly distinguishable from the image of L. pneumophila under fluorescence microscopy, except E. coli GIFU 3160.…”
Section: Discussionmentioning
confidence: 95%
“…However, several specific antibodies including a monoclonal antibody for L. pneumophila to be cross-reactive with Pseudomonas spp. or Bacteroides fragilis (2,6,11). There may be a risk of overestimation of legionellae population in environmental microbial community.…”
mentioning
confidence: 99%
“…Using antibodies from panel I of the monoclonal antibodies reported by Joly et al (Joly et al 1983) two individual studies of a substantial number of patient and environmental isolates in Canada and France (Stout et al 1988, Dournon et al 1988) demonstrated a significant association between the source of an isolate and its monoclonal subtype. Patient isolates were closely associated with the Mab2 subtype in both reports, leading to the suggestion that this subtype could be a virulence marker.…”
Section: Conventional Typing Methods (Phenotyping)mentioning
confidence: 98%
“…Early epidemiological studies made evident that serotyping of L. pneumophila was not sdficiently discriminatory for epidemiological purposes. The use of monoclonal antibodies, raised against L. pneumophila SG 1, was established by three laboratories (Joly et al 1983, McKinney et al 1983, Watkins et al 1985, each contributing to an international panel of seven antibodies (Joly et al 1986) together identifjring ten distinct subtypes of L. pneumophila SG 1 by an indirect immunofluorescence assay. This panel was used for the investigation of several outbreaks, but evidence was accumulating that enhanced discrimination by addition of genetic methods was desirable (Pfaller et al 1989, Struelens et al 1992).…”
Section: Conventional Typing Methods (Phenotyping)mentioning
confidence: 99%
“…The use of a large number of antigens and antisera from related organisms presents difficulties due to the appearance of cross-reactions. This is especially important with organisms belonging to the family Legionellaceae that have been reported to share a variety of antigens with bacteria from different levels of relatedness (Joly & Kenny, 1982;Collins et al 1983a, b;Joly, Chen & Ramsay, 1983).…”
Section: Introductionmentioning
confidence: 99%